Analysis of Responses to the Development of E-Modules to Improve Students' Critical Thinking Skills in Reaction Rate Materials in the Form of Android Applications - Sanova, Aulia; Kurniawan, Dwi Agus; Husna, Sri Muslimatul; Triani, Elza (JST (Jurnal Sains dan Teknologi), 2024)
Students' critical thinking skills in chemistry learning are generally still low, so interesting open materials are needed to improve students' critical thinking skills, one of which is e-modules. This study aims to determine the feasibility of e-modules and to determine the responses of educators and students to android-based e-modules in improving students' critical thinking skills at the rate of material reaction. This study uses a research and development (R&D) model with an R&D-based research design which stands for the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques through validation by material and media experts, as well as responses from teachers and students. The subjects of the study consisted of 30 students who used e-modules in learning. The data analysis technique used the t-test (Independent Sample T Test) to measure differences in students' critical thinking skills before and after using e-modules. The results showed a significant increase in students' critical thinking skills, with an average posttest score increasing by 13.3 points compared to the pretest (p <0.05). The conclusion of this study is that Android-based e-modules are effective in improving students' critical thinking skills. The implication of this research is that e-modules can be an interesting learning medium and can be used to support learning at school or independently at home, and have the potential to improve students' learning outcomes and critical thinking skills in the long term.